Applying an extended theory of planned behavior to sustainable food consumption - Alam, S.S. (MDPI, 2020)
The objective of this research is to identify factors affecting sustainable food consumption behavior among Malaysians. An extension of the theory of planned behavior (TPB) is used as the framework of the study. Perceived value is also added to the framework to gain an understanding of consumerâs personal factorsâ effect on sustainable food consumption. This study tested eight hypotheses on sustainable food consumption behavior with empirical data from a sample of 220 adults. The regression analysis results show that social norm, perceived value, perceived consumer effectiveness, and attitude have significant impacts on intention to consumer sustainable food. Perceived availability, perceived consumer effectiveness and intention also have significant impacts on actual behavior. The findings of this study can provide certain grounds for understanding sustainable food consumption intention and behavior. Research limitations and some guidelines for further lines of research are presented. In a global context the findings of this study is important, as consumption patterns need to be changed to meet the climate challenge. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.